2020
DOI: 10.1007/s00520-020-05307-1
|View full text |Cite
|
Sign up to set email alerts
|

Toward a theoretical understanding of young female cancer survivors’ decision-making about family-building post-treatment

Abstract: Purpose: Family-building after gonadotoxic treatment often requires in vitro fertilization, surrogacy, or adoption, with associated challenges such as uncertain likelihood of success, high costs, and complicated laws regulating surrogacy and adoption. This study examined adolescent and young adult female (AYA-F) survivors' experiences and decision-making related to familybuilding after cancer.Methods: Semi-structured interviews explored fertility and family-building themes (N=25). Based on an a priori conceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Our previous work suggested that women who experienced more intense emotions of distress and fear often described lower self-efficacy to manage risks and, at the most extreme, avoidance of fertility information and disengagement from decision-making processes [ 19 ]. These findings are consistent with the research delineating the impact of affective states on medical decision making and behavior, such that anxiety and fear tend to lead individuals to prioritize short-term gratification over long-term goals [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous work suggested that women who experienced more intense emotions of distress and fear often described lower self-efficacy to manage risks and, at the most extreme, avoidance of fertility information and disengagement from decision-making processes [ 19 ]. These findings are consistent with the research delineating the impact of affective states on medical decision making and behavior, such that anxiety and fear tend to lead individuals to prioritize short-term gratification over long-term goals [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two additional qualitative studies explored posttreatment fertility concerns [ 21 ] and family-building experiences [ 22 ] and informed our understanding of user needs. On the basis of this work, semistructured interviews (N=25) were conducted with young adult female survivors of cancer (aged 15-45 years) who received gonadotoxic treatment and were either interested in future family building or uncertain about their family-building plans [ 19 ]. Briefly, women reported high rates of unmet information needs, including uncertainty about reproductive survivorship care and where to obtain trusted information.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations